Integrating Smart Digital Quality Assurance into Internal Quality Management: A Comprehensive Review of Decision Support Systems and Organizational Resilience - Dini Pepilina; Siti Patimah; Nurul Hidayati Murtafiah (Prodi Manajemen Pendidikan Islam Universitas KH Chalim Mojokerto, 2026)
Digital transformation in quality assurance has reshaped internal quality management practices, moving organizations from manual reporting structures toward integrated, data-driven ecosystems. However, many institutions still face challenges such as fragmented system integration, low interoperability between platforms, and an overemphasis on administrative audits, which collectively reduce the effectiveness of evidence-based decision-making. This study examines the integration of Smart Quality Assurance within internal quality management using a Decision Support System (DSS) approach and explores its linkage with organizational resilience. A systematic literature review was conducted on 20 scientific articles published between 2022 and 2026, following a structured process of identification, screening, evaluation, and thematic synthesis. Findings indicate that the digitalization of quality systems through Internal Quality Assurance Systems, Total Quality Management, ISO 9001:2015 frameworks, and artificial intelligence-based applications enhances audit efficiency, accelerates evaluation cycles, and improves the accuracy of managerial decision-making. DSS integration further demonstrates strong potential in enabling predictive analytics and supporting adaptive, proactive quality governance. In addition, successful implementation is strongly influenced by digital literacy levels, infrastructure readiness, and the degree of integration across institutional information systems. This study contributes by synthesizing an integrated conceptual framework that connects Smart Quality Assurance, DSS-based decision-making, and organizational resilience, offering a consolidated perspective that can guide future research and practical implementation in higher education and organizational quality systems.